Effect of Ulva lactuca extract on growth and proximate composition of Vigna unguiculata l. Walp - Gireesh R; CK, Haridevi; Joseph, Salikutty (Journal of Research in Biology, 2011)
As organic farming gains more attention, seaweed cultivation and its utilization may be an economical approach in agricultural production. The effect of seaweed Ulva lactuca extract on growth and proximate composition of Vigna unguiculata L. Walp was studied. Seedlings of V. unguiculata soaked with seaweed extract performed better when compared to seedlings with water soaked control. The low concentration (20%) of aqueous seaweed extract promoted seedling growth in terms of shoot length, root length, fresh and dry weight and chlorophyll and carotenoids content. The biochemical constitutents show similar patterns with protein content of shoot and root, amino acid of shoot and root, α-amylase and β-amylase activities being higher with seaweed extract in V. unguiculata. The seaweed extract in these experiments showed as biological fertilizer, which is a nontoxic and ecofriendly supplement to chemical fertilizer for many crops intended to attain higher yields